PEMAHAMAN ḤADITH (Definisi, Aliran, dan Afilisasi) - Hariono, Duwi (UNIVERSUM, 2017)
The terms in hadith study is often ambiguous and difficult to differentiate. As the terms of hadith, sunah, khabar, and atsar are often used at the same time. For hadith observers, it becomes serious problem and complicated since those terms have significant difference. Hence, the same usage of those terms cannot be accepted. One of the debatable issues in discussing hadith study is about disagreement in defining the term of hadith understanding. The hadith scholars mention it in three terms: fiqh al-ḥadith, fahm al-ḥadith dan naqd al-ḥadith. Each term has different perception related to its scope and limitation. One should be underlined that although those terms are different, the purposes are same namely hadith understanding activities. This article discusses the definition of fiqh al-ḥadith, fahm al-ḥadith dan naqd al-ḥadith and their sects and affiliation of hadith understanding. Keywords: Fiqh al-ḥadith, fahm al-ḥadith, naqd al-ḥadith, sects, affiliation